Promoting vision and hearing aids use in an intensive care unit. Issue 1 (9th February 2015) - Zhou, Qiaoling; Faure Walker, Nicholas
Abstract: Vision and hearing impairments have long been recognised as modifiable risk factors for delirium.[1, 2, 3] Delirium in critically ill patients is a frequent complication (reported as high as 60% to 80% of intensive care patients), and is associated with a three-fold increase in mortality and prolonged hospital stay.[1] Guidelines by the UK Clinical Pharmacy Association recommend minimising risk factors to prevent delirium, rather than to treat it with pharmacological agents which may themselves cause delirium.[4] To address risk factors is a measure of multi-system management, such as sleep-wake cycle correction, orientation and use of vision and hearing aids, etc.[5] We designed an audit to survey the prevalence and availability of vision and hearing aids use in the intensive care unit (ICU) of one university hospital. The baseline data demonstrated a high level of prevalence and low level of availability of vision /hearing aid use. We implemented changes to the ICU Innovian assessment system, which serves to remind nursing staff performing daily checks on delirium reduction measures. This has improved practice in promoting vision and hearing aids use in ICU as shown by re-audit at six month. Further amendments to the Innovian risk assessments have increased the rate of assessment to 100% and vision aid use to near 100%.